No Evidence for “Break-Induced Replication” in a Higher Plant – But Break-Induced Conversion May Occur - Schubert, Ingo; Schubert, Veit; Fuchs, Jörg (Frontiers in Plant Science, 2011)
‘Break-induced replication’ (BIR) is considered as one way to repair DNA double-strand breaks (DSBs). BIR is defined as replication of the proximal break-ends up to the end of the broken chromosome using an undamaged homologous double-stranded template and mimicking a non-reciprocal translocation. This phenomenon was detected by genetic experiments in yeast. BIR is assumed to occur also in mammals, but experimental evidence is not yet at hand. We have studied chromosomes of the field bean, Vicia faba L., as to the occurrence of BIR after DSB induction during S and G2 phase. Simultaneous incorporation of the base analogue ethynyldeoxyuridine (EdU) revealed no chromosomal replication pattern indicative of BIR. Thus, if occurring at all, BIR does not play a major role for DSB repair in higher plants with large chromosome arms. However, the frequency of interstitial asymmetric EdU incorporation within heterochromatic regions, visible on metaphase chromosomes, increased after chromosome breakage during S and G2 phase. Such asymmetric labelling could be interpreted as conservative replication up to the next replicon, circumventing a DSB and yielding an interstitial conversion-like event.